AKULTURASI ISLAM DAN BUDAYA MELAYU (Simbolisme Tradisi Kematian Orang Melayu Palembang) - Haljuzila Fasari P (Program Studi Manajemen Dakwah, Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2018)
This article discusses how Islam perceived, developed, and practiced by the Malay-Palembangnese in the context of death traditions. Islam and local culture influenced each other and this was shown through symbols. This article denotes the acculturation process between Islam and Malay-Palembang culture on death traditions. This article also emphasizes the contestative and gradual spread of Islam in Malay-Palembangnese society. The author found that the Malay-Palembangnese possesses distinctive characters on their death traditions that are different from the concepts of Geetrz’s, Woodward’s, Nur Syam”s, and Ricleft’s theories. Keyword: Acculturation, Islam, Culture, Malay, Tradition, Life Cycle, and Palembang.